2019
DOI: 10.4103/jfmpc.jfmpc_315_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of breast self-examination amongst female IT professionals in Silicon Valley of India

Abstract: Introduction:Breast cancer is one of the leading causes of cancer deaths among women in India today. Overall outcome of this disease is largely dependent on early detection and medical intervention. Breast self-examination (BSE) is an easy, cost effective, and safe method of screening for the same.Materials and Methods:A cross-sectional descriptive questionnaire-based study was conducted among female IT professionals and their scores in the fields of knowledge, attitude, and practice were calculated. The score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 13 publications
4
13
0
1
Order By: Relevance
“…Thus, students having good knowledge on BSE were 12.02 times more likely to perform better BSE practice compared with those with poor knowledge. This finding is in agreement with results reported from studies conducted in India [ 26 ] and Nigeria [ 29 ]. It is also aligned with the findings of local studies done in Addis Ababa [ 27 ], Debre Tabor [ 33 ], Debre Birhan University [ 16 ], and West Shoa [ 34 ] and SR and MA in Ethiopia [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, students having good knowledge on BSE were 12.02 times more likely to perform better BSE practice compared with those with poor knowledge. This finding is in agreement with results reported from studies conducted in India [ 26 ] and Nigeria [ 29 ]. It is also aligned with the findings of local studies done in Addis Ababa [ 27 ], Debre Tabor [ 33 ], Debre Birhan University [ 16 ], and West Shoa [ 34 ] and SR and MA in Ethiopia [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, about one in six (17.3%) of students had better BSE practice. The finding is similar with that reported in the study done in Silicon Valley of India (19.1%) [ 26 ], nationwide survey in Korea (16.1%) [ 20 ], and Addis Ababa university in Ethiopia (21.4%) [ 27 ]. The agreement in magnitude might be ascribed to the nonhealth profession of the respondents in common [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…Early detection plays a key role in preventing BC mortality and increases the 5-year survival rate of patients from 56 to 85% (8). Studies have shown that low levels of knowledge, fear, and psychosocial barriers are the main reasons for women not participating in BC screening programs (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned studies, about 3.7% of women undergo (Monfared et al, 2017). In western countries, the mortality rate of this disease has been greatly reduced due to the use of these methods by the majority of women (Kalliguddi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%